Men's Sheds and the experience of depression in older Australian men - Culph, J.; Wilson, N.; Cordier, Reinie; Stancliffe, R. (Wiley-Blackwell Publishing Asia, 2015)
Background/aim: Men’s Sheds are community spaces where, usually, older men can socialise as they participate in a range of woodwork and other activities. There is currently little research evidence supporting the anecdotally reported mental health and wellbeing benefits of Men’s Sheds. This research project investigated how older men with self-reported symptoms of depression experience theirparticipation in Men’s Sheds.Methods: This study included in-depth interviews and administration of the Beck Depression Inventory-II with 12 men from 3 Men’s Sheds, triangulated with observation of the different shed environments. Interviews explored how participation in the Men’s Shed, living in a regional area, and retirement intersected with experiences of depression. Participants had either self-reported symptoms of depression or a diagnosis of depression.Results: The findings from this study support the notion that participation at Men’s Sheds decreases self-reported symptoms of depression. Beck Depression Inventory-II scores showed that most participants were currently experiencing minimal depression. The Men’s Sheds environment promoted a sense of purpose through relationships and in the sharing of skills, new routines, motivation, and enjoyment for its members. The shed encouraged increased physical activity and use of cognitive skills. Finally, participants reported feelings of pride and achievement which had an impact on their sense of self-worth.Conclusion: Men’s Sheds provide an opportunity to promote health and wellbeing among retired men. The shed’s activity and social focus offers a way to help men rediscover purpose and self. Further research is required to measure symptoms of depression before and after participation in Men’s Sheds.